Case report: A successful live birth after in vitro fertilization and embryo transfer in a patient with endometrial cancer who was treated conservatively - Yifan Fan; Yifan Fan; Yifan Fan; Hui Song; Hui Song; Hui Song; Xu Chen; Xu Chen; Xu Chen; Pei Zhang; Jingwen Si; Hui Dong; et al. (Frontiers in Oncology)
ObjectiveTo describe a patient conceiving with in vitro fertilization and embryo transfer(IVF-ET) after conservative treatment of early stage endometrial cancer.PatientA 31-year-old multiparous woman diagnosed with highly-differentiated (G1) endometrial adenocarcinoma (grade IA).Intervention(s)After four courses of conservative treatment each followed by hysteroscopic biopsy and endometrial curettage,assisted reproductive technology was performed.Main outcome measure(s)Successful pregnancy and delivery without residual endometrial cancer.Results(s)A healthy normal female infant with a birth weight of 3,690 g was born by cesarean section at 38 + 2 weeks’ gestation. No residual malignant cells was detected on a biopsy during cesarean section.Conclusion(s)Conservative fertility-sparing treatment are crucial for young patients with early stage endometrial cancer. Assisted reproductive technologies may be considered to assist such patients to conceive as soon as possible.